Roots, shoots, buckets & boots: gardening together with children - Lovejoy, Sharon, 1945- (New York : Workman Pub., 1999)
Presents 12 theme gardens for parents and children to grow together, including the pizza patch, the sunflower house, the moon garden, and the flowery maze.
Includes bigliographical references (p. 158-159).
Keywords: Children's gardens; Gardening